2003
DOI: 10.1117/12.476550
|View full text |Cite
|
Sign up to set email alerts
|

Scalability of buried microreflector light-emitting diodes for high-current applications

Abstract: The combination of wafer soldering using metal layers and the introduction of buried micro-reflector structures has proven to be a promising approach to fabricate high brightness, substrate-less LEDs in the AlGaInP material system. In addition to the enhanced light output, the scalability of this approach has been predicted as a major advantage. In contrast to other approaches, larger area LEDs can be fabricated without altering the epitaxial structure and thickness of layers simply by offering a larger area f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…Illek et al 39 demonstrated a TF AlGaInP LED with an array of buried coneshaped microreflectors. The LED structure is shown schematically in Fig.…”
Section: Thin-film Ledsmentioning
confidence: 99%
See 4 more Smart Citations
“…Illek et al 39 demonstrated a TF AlGaInP LED with an array of buried coneshaped microreflectors. The LED structure is shown schematically in Fig.…”
Section: Thin-film Ledsmentioning
confidence: 99%
“…In contrast to TS-LEDs, very thick window layers in order to increase sidelight extraction are not required. 37,39 For devices emitting at 650 nm, quantum efficiencies of 31% 40 and 40% 41 have been reported. Despite the presence of etched regions, the forward voltage is below 2.0 V at a forward current I f ϭ10 mA.…”
Section: Thin-film Ledsmentioning
confidence: 99%
See 3 more Smart Citations